Sediaan Topikal Gel Dari Aloe Barbadensis Sebagai Terapi Komplementer Penyembuh Luka Berbahan Alam - Ratnasantasyacitta, Elizabeth Sri Primasari (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The aloe vera plant (Aloe barbadensis Miller) can be made in various dosage forms, one of which is a gel preparation. The part of aloe vera which is the mucous gel that is obtained from the inside of the aloe vera leaf is commonly used. One of the benefit of aloe vera is as a wound healer because it contains saponins, tannins, mannose-6-phosphate, and polysaccharides. The mechanism of these compounds are promoting fibroblast proliferation, production of hyaluronic acid and hydroxyproline in fibroblasts, which play an important role in the wound healing process. The aim of this narrative review is to determine the activity of aloe vera in a gel preparation as a wound healer. Several previous studies have shown the existence of wound healing activity in experimental animals treated with aloe vera extract in a gel preparation. Aloe vera in the gel preparation is expected to be an alternative therapy or complementary therapy derived from natural ingredients as a wound healer because it is easy to obtain and easy to use.